KELAYAKAN MODUL PEMBELAJARAN IPA BERBASIS POTENSI LOKAL PADA POKOK BAHASAN PERUBAHAN BENDA DI SMPN 1 SEMBORO KABUPATEN JEMBER - Zakaria Sandy Pamungkas; Sri Wahyuni; Trapsilo Prihandono (JURNAL PEMBELAJARAN FISIKA, 2017)
The purpose of this research is to examine the eligibility of integrated science learning module based on local potential on the topic of objects transformation.This research were developed by Borg and Gall method that modified into four step, that is : (1) front-end analysis, (2) designing module, (3) validation and revision, and (4) testing module and final revision. The design of field testing is The One Group Pretest-Posttest Design.The results show thatintegrated sciences module based potential local on the topic of objects transformation is proper to be applied in learning. This can be seen from the validation assesment criteria gets valid with a assesment scores reached 3,8 which is proper with BSNP’s criteria. The practically assesment shown from percentage 94,44% with a criteria pratice, indicating that the students are very gave a positive response, The effectiveness assesment shown from improvement student learning outcomes showed in the medium category indicated by the calculation of the gain score 0,4735. It could be concluded that the sciences module based potential local on the topic of objects transformation fit for use and effectively to increae the result of student learning. Keywords: effectiveness, practicality,local potential, validity